Answer:
Additive inverse is (7y² - x²y + 3xy + 7x²).
Step-by-step explanation:
Let the additive inverse of the given polynomial be Y.
Therefore as per definition of additive inverse of any polynomial the addition of a polynomial and additive inverse of any polynomial is always zero.
So Polynomial + additive inverse polynomial = 0
(-7y² + x²y - 3xy - 7x²) + Y = 0
Y = -(-7y² + x²y - 3xy - 7x²) = (7y² - x²y + 3xy + 7x²)
So the additive inverse of the polynomial will be (7y² - x²y + 3xy + 7x²).
Answer:
The answer is A
Step-by-step explanation:
The additive inverse is basically the opposite symbol for the numbers.
So, therefore:
What is the additive inverse of the polynomial?
-7y^2 + x^2y - 3xy - 7x^2
The answer to this would be
7y^2 - x^2y + 3xy + 7x^2
Answer:
The missing side is 5
Step-by-step explanation:
you would do 4^2 + 3^2 = c^2
16+9+c^2
25=c^2
5=c